2021
DOI: 10.1002/ccd.29777
|View full text |Cite
|
Sign up to set email alerts
|

Directional atherectomy before paclitaxel coated balloon angioplasty in complex femoropopliteal disease: The VIVA REALITY study

Abstract: Background: Drug coated balloon (DCB) angioplasty significantly reduces reintervention rates in patients with symptomatic femoropopliteal peripheral artery disease (PAD). However, stand-alone DCB use in long, severely calcified lesions is frequently associated with vessel recoil and/or high-grade dissections necessitating provisional stent implantation.Objectives: Assess the safety and effectiveness of a vessel preparation strategy with directional atherectomy (DA) prior to DCB angioplasty in patients with sym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 44 publications
(17 citation statements)
references
References 31 publications
0
16
0
1
Order By: Relevance
“…The recent REALITY single-arm study (N ¼ 102 patients) reported on the safety and effectiveness of directional atherectomy followed by DCB therapy to treat long, severely calcified femoropopliteal PAD. 33 Although the primary patency rate at 1 year was 76.7% in this challenging lesion cohort, the rates of angiographic complications remained high (major dissection: 14.3%; perforation: 3.1%; distal embolization despite the use of embolic protection: 12.8%; bailout stenting: 8.8%). Cross-trial comparisons to the Disrupt PAD III are difficult, and randomized trials are needed to assess the comparative outcomes between IVL and atherectomy in the treatment of calcified PAD.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…The recent REALITY single-arm study (N ¼ 102 patients) reported on the safety and effectiveness of directional atherectomy followed by DCB therapy to treat long, severely calcified femoropopliteal PAD. 33 Although the primary patency rate at 1 year was 76.7% in this challenging lesion cohort, the rates of angiographic complications remained high (major dissection: 14.3%; perforation: 3.1%; distal embolization despite the use of embolic protection: 12.8%; bailout stenting: 8.8%). Cross-trial comparisons to the Disrupt PAD III are difficult, and randomized trials are needed to assess the comparative outcomes between IVL and atherectomy in the treatment of calcified PAD.…”
Section: Discussionmentioning
confidence: 72%
“…31 Although not evaluated in Disrupt PAD III, the use of atherectomy to treat calcified PAD has been reported in small randomized and single-arm studies. 15,16,[32][33][34][35] Atheroablative technologies can be effective in debulking vascular calcium and improving luminal area, but procedural complications remain a concern. The recent REALITY single-arm study (N ¼ 102 patients) reported on the safety and effectiveness of directional atherectomy followed by DCB therapy to treat long, severely calcified femoropopliteal PAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 In the multicenter VIVA REALITY study, DAART was evaluated in 102 patients with complex, long FP stenosis or occlusions (17.9 ± 8.1 cm) with moderate to heavy calcification. 5 Procedural-related adverse events such as flow-limiting dissection or perforation occurred in 14 patients; all resolved with EVT during the index procedure with provisional stenting in 8.8%. Twelve-month PP was 76.7% and freedom from CD-TLR was 92.6% with one major amputation.…”
mentioning
confidence: 98%
“…Similarly, in the Directional Atherectomy Followed by a Paclitaxel‐Coated Balloon to Inhibit Restenosis and Maintain Vessel Patency (DEFINITIVE AR) pilot study ( n = 121), DAART was seen to be both safe and effective in complex femoral‐popliteal (FP) disease, although the study was not sufficiently powered to make a randomized comparison between DAART and DCB alone for long‐term outcomes and 20% of patients were deemed unsuitable for DCB alone 4 . In the multicenter VIVA REALITY study, DAART was evaluated in 102 patients with complex, long FP stenosis or occlusions (17.9 ± 8.1 cm) with moderate to heavy calcification 5 . Procedural‐related adverse events such as flow‐limiting dissection or perforation occurred in 14 patients; all resolved with EVT during the index procedure with provisional stenting in 8.8%.…”
mentioning
confidence: 99%